PENGARUH KARAKTERISTIK PEKERJAAN DAN LINGKUNGAN KERJA FISIK TERHADAP KEPUASAN KERJA KARYAWAN DI DINAS KEARSIPAN DAN PERPUSTAKAAN PROVINSI SUMATERA BARAT - Putri Burhami; Rini Sarianti; Dessi Susanti (Jurnal Ecogen, 2018)
Abstract: This study aims to examine the effect of job characteristics and physical work environment on job satisfaction in the Archives and Library Service of West Sumatra Province. This research is a causative descriptive study. The population in this study consisted of all civil servant employees using primary data and secondary data. The analytical method that is used  multiple regression analysis using SPSS version 21. To test hypotheses using statistical t test with a level of α of 5%. The results of this study indicate that 1) job characteristics do not have a significant influence on employee job satisfaction in the Department of Archives and Libraries of West Sumatra Province 2) Physical Work Environment has a significant effect on employee job satisfaction in the Department of Archives and Libraries of West Sumatra ProvinceKeyword: job characteristics, physical work environment and job satisfaction